2008
DOI: 10.1890/07-1776.1
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependent Effects of Fishing: Variation in Trophic Cascades Across Environmental Gradients

Abstract: Abstract. Marine reserves provide a large-scale experimental framework to investigate the effects of fishing on food web dynamics and how they vary with environmental context. Because marine reserves promote the recovery of previously fished predators, spatial comparisons between reserve and fished sites are often made to infer such effects; however, alternative explanations for differences between reserve and fished sites are seldom tested (e.g., environmental variation among sites). We investigated the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 64 publications
(87 reference statements)
3
121
2
Order By: Relevance
“…5B). As other recent studies have shown, marine reserve responses may be context dependent and spatially variable as a result of differences in physical and environmental factors, reserve size, the degree and time of reserve protection, and the intensity of fishing pressure outside (37,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 93%
“…5B). As other recent studies have shown, marine reserve responses may be context dependent and spatially variable as a result of differences in physical and environmental factors, reserve size, the degree and time of reserve protection, and the intensity of fishing pressure outside (37,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 93%
“…At high disturbance, such as a forest fire or human interventions, all species are at risk. After this seminal paper was published, other investigators reported context-dependent responses in a wide variety of marine [13] and freshwater [14,15] ecosystems. Because context dependency complicates our ability to generalize about important ecological processes, it has undoubtedly contributed to many contentious debates in ecology.…”
Section: Context-dependent Responsesmentioning
confidence: 99%
“…Stable isotopes of nitrogen, carbon, and, more recently, sulfur have added considerably to our understanding, because they trace sources of nutrients to consumers (d 13 C and d 34 S) and measure relative trophic position of the biota (d 15 N) [24]. A popular application of stable isotopes in ecotoxicology is using d 15 N to quantify the rates at which contaminants biomagnify, because concentrations of POPs or methyl Hg are significantly and positively related to trophic position [24][25][26].…”
Section: Fate Of Contaminantsmentioning
confidence: 99%
“…However, a study at a nearby location also found low rates of grazing, although densities of sea urchins were markedly higher (5.8 m -2 ; Vanderklift & Wernberg 2008). There is increasing evidence that, although grazing by sea urchins undoubtedly modifies ecosystems at some places, density of sea urchins alone does not lead to high rates of grazing, as many species assume a drift-feeding behaviour (Castilla & Moreno 1982, Harrold & Reed 1985, Day & Branch 2002a, Shears et al 2008.…”
Section: Low Rates Of Grazing By Fish and Sea Urchinsmentioning
confidence: 99%